Neuraminidase Injections in Rabbits - Grøttum, A. K; Jeremic, M (Thrombosis and Haemostasis, 1973)
Two types of neuraminidase from CL perfringens were injected intravenously in rabbits. Blood platelet electrophoretic mobility was markedly reduced 4 hours after the injection of the enzyme. A marked thrombocytopenia developed gradually with a mean lower level of 55 and 27% of the preinjection number 48 hours after the injec- - tion. White blood cell count and factors V and VIII were reduced.The results indicate that rabbit platelets with a reduced surface charge5 due to cleavage of sialic acid from the platelet membrane, are not immediately aggregated, trapped or destroyed in vivo. We suggest that the enzyme-induced platelet membrane changes rendered the platelets more susceptible to destruction in the reticuloendothelial system with appearance of thrombocytopenia after some hours.